Postural Discomforts in Children due to Heavy Backpack - Shahbaz, Areesha; Sadaf, Ambreen; Saleem, Sadia; Rubina, Chandni; Ali, Yasir; Khan, Tayyaba (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: To find the postural discomforts in school-going children due to heavy backpacks. METHODOLOGY: The study was designed as a cross-sectional descriptive study. This study was conducted in private schools in Lahore. Data was collected using a purposive sampling technique from September 2021 to February 2022. A sample size of 196 students was selected for this study. A nordotic musculoskeletal questionnaire was used. The children were chosen using the purposive sampling method. Students in grades 5 through 10 are included, carrying bags with one or both shoulders. Students of all genders were included with independent standing on the weighing scale. The study excluded students with metabolic abnormalities or musculoskeletal complaints caused by pathological, orthopedic, or hereditary factors. SPSS 21.0 was used for analysis. RESULTS: The result shows that about 107(54.6%) students have neck pain due to wearing backpacks. About 160(81%) students have pain in both shoulders. Only 3(1.5%) students had pain in hand/wrist. 109(55.6%) students had pain in the upper back. 121(61.7%) students had pain in lower back, 107(54.6%) students experienced pain in upper back, 69(35.2%) students had pain in the hip/thighs, 54(27.6%) students had pain in their knees. 78(39.8%) students had pain in ankle/feet. CONCLUSION: Children's shoulders, necks and backs can get chronically strained from carrying a hefty backpack, resulting in pain. The backpack's weight, how it is worn, and other factors all impact how stable a student's posture is, which leads to the conclusion that a child wearing a backpack has postural impacts on their body posture.